Digipelaamista rautaesiripun takana - Suominen, Jaakko (Tekniikan Waiheita, 2019)
Jaroslav Švelch. 2018. Gaming the Iron Curtain. How Teenagers and Amateurs in Communist Czechoslovakia Claimed the Medium of Computer Games. Cambridge, MA: MIT Press, 351 sivua.